Sexual dimorphism in striped dolphin (Stenella coeruleoalba) crania from South Africa. Issue 4 (25th July 2016) - Conry, Danielle S.; Pistorius, Pierre A.; Plön, Stephanie; Hofmeyr, G. J. Greg
Abstract: This study assessed the extent of sexual dimorphism in striped dolphin ( Stenella coeruleoalba ) cranial size and shape off the South African coast. Dorsal and ventral features of 60 striped dolphin crania from both the western and eastern coasts of South Africa were analyzed using landmark‐based geometric morphometrics. Although there was no evidence of dimorphism in cranial size, evidence for small, but significant, variation in both dorsal and ventral cranial shape was found between the sexes. The observed dimorphism was partly associated with changes in shape around the temporal fossa, occipital condyle and supraoccipital bone, the nasal bone, and the paraoccipital process and basiocciptal. The temporal fossa serves as an attachment point for the temporal muscle, which functions to close the lower jaw, and the occipital area serves as the anterior insertion of the epaxial muscles, which power the upstroke of the flukes during swimming. Both the paraoccipital process and basiocciptal are associated with the functioning of the hyoid apparatus, which serves as an attachment point for muscles and ligaments involved in feeding and sound production. These findings suggest the possibility of differences in diet, foraging behavior, vocalizations, and locomotion between the sexes of this species.